Peningkatan Repurchase Intention melalui Dimensi Service Quality pada Pelanggan Mochi Delleza di Semarang - Dita Armita; Heru Sulistyo (ARZUSIN, 2026)
Increasingly intense competition in the food and beverage industry requires businesses to retain customers by improving service quality, including among culinary micro, small, and medium enterprises (MSMEs). Mochi Delleza, a contemporary dessert MSME in Semarang City, faces fluctuating customer numbers, indicating that repurchase intention has not yet been optimized. This study aims to analyze the influence of the service quality dimensions—tangibles, empathy, responsiveness, reliability, and assurance—on customers’ repurchase intention toward Mochi Delleza in Semarang. A quantitative approach with a survey method was employed by distributing questionnaires to 100 customers selected using purposive sampling. The data were analyzed using Partial Least Square–Structural Equation Modeling (PLS-SEM) with the SmartPLS 4 software. The results show that, individually, the reliability and assurance dimensions have a positive and significant effect on repurchase intention, whereas tangibles, empathy, and responsiveness do not have a significant effect. These findings indicate that service reliability and customer trust assurance are the main factors driving repurchase intention. The study concludes that increases in customers’ repurchase intention toward Mochi Delleza are more strongly influenced by consistency in service delivery and the sense of security provided, with practical implications for management to focus strategies on strengthening service reliability and employee competence in order to reinforce customer loyalty.